Exploring SERS from complex patterns fabricated by multi-exposure laser interference lithography. (14th May 2021) - Kim, Seong Jae; Hwang, June Sik; Park, Jong-Eun; Yang, Minyang; Kim, Sanha
Abstract: Designing uniform plasmonic surfaces in a large area is highly recommended for surface-enhanced Raman scattering (SERS). As periodic morphologies exhibit uniform SERS and optical tunability, diverse fabrication methods of periodic nanostructures have been reported for SERS applications. Laser interference lithography (LIL) is one of the most versatile tools since it can rapidly fabricate periodic patterns without the usage of photomasks. Here, we explore complex interference patterns for spatially uniform SERS sensors and its cost-effective fabrication method termed multi-exposure laser interference lithography (MELIL). MELIL can produce nearly periodic profiles along every direction confirmed by mathematical background, and in virtue of periodicity, we show that highly uniform Raman scattering (relative standard deviation <6%) can also be achievable in complex geometries as the conventional hole patterns. We quantitatively characterize the Raman enhancement of the MELIL complex patterns after two different metal deposition processes, Au e-beam evaporation and Ag electroplating, which results in 0.387 × 10 5 and 1.451 × 10 5 in enhancement factor respectively. This alternative, vacuum-free electroplating method realizes an even more cost-effective process with enhanced performance. We further conduct the optical simulation for MELIL complex patterns which exhibits the broadened and shifted absorption peaks. This result supports the potential of the expanded optical tunability of the suggested process.